Isolation and Identification of Infectious Agents of Bacterial Flacherie in Bombyx mori (L) - Selvi , G. S. Anantha (Microbiology and Biotechnology Research: An Overview Vol. 1, 2025)
Sericulture is a highly cost-effective entrepreneurship providing opportunities for farmers to accelerate stable and gainful profits. The primary constraint in silk production is the occurrence of silkworm diseases, particularly Bacterial Flacherie. This disease is caused by a variety of bacteria, including Bacillus subtilis, Streptococcus pneumoniae, Staphylococcus aureus, Pseudomonas fluorescens, and Bacillus cereus. These pathogens have been identified and isolated from infected silkworms using techniques such as colony morphology, staining properties, and biochemical tests. The main objective of this study is to isolate and identify the causative agents of Bacterial Flacherie and this study can help in developing effective control measures, thereby reducing the economic losses caused by disease outbreaks of the specific pathogens responsible for Bacterial Flacherie in Bombyx mori. The significance of this work lies in its potential to contribute to the improvement of silkworm health and productivity.